Meningkatkan Hasil Belajar IPS melalui Model Pembelajaran Kooperatif Tipe Numbered Head Together di Kelas IV Sekolah Dasar - Muhammad Ilham; Irmawati Irmawati (Diniyah: Jurnal Pendidikan Dasar, 2021)
This study aims to improve student learning outcomes in the form of economic activity in Class IV SD Negeri 7 Sawerigadi Kab. West Muna. This study is classroom action research which consists of two cycles. The subjects in this study were teachers and fourth grade students of SD Negeri 7 Sawerigadi who were registered in the 2018/2019 academic year with a total of 20 students. The research procedure consists of planning, action, observation, evaluation and reflection. The data in this study are qualitative data (data on teacher and student activities) and quantitative data (data on student learning outcomes obtained through test results). The results showed an increase in student learning outcomes when the teacher used the Numbered Head Together (NHT) cooperative learning model in social studies learning. In the first cycle of student learning completeness as many as 12 people or 60% with an average value of 72.0. In the second cycle, student learning completeness increased to 19 people or 90% with an average value of 87.5.Keywords: NHT, social studies, cooperative learning